Uji Fenotipik Deteksi Enzim ESBL, AmpC dan Karbapenemase pada Bakteri Enterobacteriaceae - Ade Dharmawan; Nicolas Layanto (Jurnal Kedokteran Meditek, 2019)
Organisms that express extended-spectrum β-lactamase (ESBLs) such as Enterobacteriaceae have been increasing for the past forty years. Organisms that express this enzyme can hydrolyze oxyminocephalosporins and monobactam,but can be inhibited using β-lactam inhibitors. There are various types of enzymes that contribute to cephalosporin and monobactam resistances, such as AmpC β-lactamase, and carbapenemase enzymes. Polymerase Chain Reaction (PCR) is an accurate method for detecting ESBL, but this method is a genotypic method that requires a specialized instrument. Therefore there is a need for a phenotypic method to detect ESBL, AmpC and Carbapenemase that can be conducted in various laboratories.